Implementation of Moral Values Through Short Story Book “Testing Honesty” by Lara Firdana in Early Children - Nurma Annisa Azzahra (AT-TURATS, 2022)
Early childhood is in a golden age throughout the age range of human development. This period is a sensitive period, during this time the child is especially easy to receive stimuli from the environment. There are six aspects of development in early childhood that must be stimulated so that early childhood development can develop optimally. One of the efforts that educators and parents can do is to familiarize children with moral values. Moral is behavior about good or bad that will be accepted through one's actions, attitudes, obligations, morals and character. Each page of the short story contains values that can be applied to children, one of which is moral values. Children will benefit from the moral message conveyed by the author of the story content of a short story. This research was conducted using a qualitative method with a descriptiv approach aimed at analyzing the intrinsic elements of the mandate and moral values of the short story. The results of the short story analysis show that there are four moral values conveyed from short stories that test honesty, namely family morals, honesty morals, curiosity morals, and social care morals.